2021
DOI: 10.3389/fnut.2021.775382
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Oleic and Palmitic Acids on Lipid Droplet-Mitochondria Interaction in the Hepatic Cell Line HepG2

Abstract: Fatty acid overload, either of the saturated palmitic acid (PA) or the unsaturated oleic acid (OA), causes triglyceride accumulation into specialized organelles termed lipid droplets (LD). However, only PA overload leads to liver damage mediated by mitochondrial dysfunction. Whether these divergent outcomes stem from differential effects of PA and OA on LD and mitochondria joint dynamics remains to be uncovered. Here, we contrast how both fatty acids impact the morphology and interaction between both organelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 52 publications
(109 reference statements)
5
30
1
Order By: Relevance
“…In HepG2 cells, oleic acid led to TAG accumulation, larger lipid droplets and a closer proximity between lipid droplets and mitochondria than when cells were treated with bovine serum albumin (control) or palmitic acid. Additionally, mitochondria from the cells added oleic acid and reduced the FA oxidation capacity compared to the control or palmitic acid-treated cells [43]. These results match well with observations from the present study and imply that increased oleic acid, which was elevated when EPA + DHA decreased, can contribute to lipid accumulation in the liver.…”
Section: Discussionsupporting
confidence: 91%
“…In HepG2 cells, oleic acid led to TAG accumulation, larger lipid droplets and a closer proximity between lipid droplets and mitochondria than when cells were treated with bovine serum albumin (control) or palmitic acid. Additionally, mitochondria from the cells added oleic acid and reduced the FA oxidation capacity compared to the control or palmitic acid-treated cells [43]. These results match well with observations from the present study and imply that increased oleic acid, which was elevated when EPA + DHA decreased, can contribute to lipid accumulation in the liver.…”
Section: Discussionsupporting
confidence: 91%
“…The liver is the central organ for the metabolism of saturated fatty acids such as palmitic acid [13]. Moreover, various in vitro and in vivo studies have shown palmitic acid can induce increased lipid droplet accumulation in hepatocytes [13][14][15][16][17]. These findings support the hypothesis that a palmitic-acid-based nanocarrier may accumulate in the hepatocytes.…”
Section: Introductionsupporting
confidence: 53%
“…With this precedence, we elected to utilize the well-documented model of treating these cells with sodium palmitate, a sodium salt of PA, for 24 h using bovine serum albumin (BSA) as a carrier and solubilizer ( Park et al, 2015 ; Alsabeeh et al, 2018 ). Sodium palmitate has been used extensively to model fatty acid exposed livers due to its ability to recapitulate lipid accumulation and steatosis in cells, and as such, it provides a basis to study lipid-induced copper misregulation ( Gómez-Lechón et al, 2007 ; Eynaudi et al, 2021 ). A 24-h treatment of HepG2 with 250 μM PA indeed resulted in an elevation of ATP7B expression as measured by western blotting ( Figure 1A ; Supplementary Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
“…In support of the changes in mitochondrial fission, we observe changes in mitochondrial membrane potential. This potential was measured by the JC-1 dye, which aggregates in healthy mitochondria and is monomeric in depolarized membranes, is perturbed by the accumulation of fatty acids in the cell as previously reported ( Eynaudi et al, 2021 ). The changes show a slight increase at 1 h that subsides at 6 h but becomes significantly increased at 12 ( p = 0.0109) and 24 h ( p = 0.00597), all of which coincides with changes in copper metabolism ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%